Hello, Universe - Kelly, Erin Entrada (New York, NY : Greenwillow Books, an imprint of HarperCollinsPublishers, 2017)
Lives of four misfits are intertwined when a bully's prank lands shy Virgil at the bottom of a well and Valencia, Kaori, and Gen band together in an epic quest to find and rescue him.
Keywords: Friendship in children -- Juvenile fiction; Missing children -- Juvenile fiction; Bullying -- Juvenile fiction; Hearing impaired -- Juvenile fiction; Psychic ability -- Juvenile fiction; Sisters -- Juvenile fiction; Friendship -- Fiction; Lost children -- Fiction; Bullying -- Fiction; Hearing impaired -- Fiction; Psychic ability -- Fiction; Sisters -- Fiction; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance; JUVENILE FICTION / Social Issues / Special Needs